Comparative evaluation of effect of different premedication agents on efficacy of Articaine: A randomized contol trial - Anjali Sharma; Rohit Sharma; Madhurima Sharma; John Johnson Panadan; M Abbas Ansari; Sasmita Dalai (Journal of Oral Biology and Craniofacial Research)
Type of study: Original Research. Aims: To comparatively evaluate the effect of different premedication agents on the efficacy of 4% Articaine in teeth with symptomatic irreversible pulpitis. Materials and methods: The primary objective of our study is to evaluate the effect of premedication agents on efficacy of Articaine as an oral anesthetic. Our secondary objective is to comparatively evaluate the efficacy of Diclofenac patch, Ibuprofen tablet, Paracetamol tablet and Placebo as a premedication agent. Patients with 25–40 years age, no systemic disease, no history of medication for that complaint, with pain on Heft Parker Visual Analog Scale between 55 mm and 170 mm (VAS), no tenderness on percussion, cold test and EPT negative- Positive, giving proper consent, coming to the Department of Conservative Dentistry and Endodontics were allowed to participate. The exclusion criteria include the following- Non-vital teeth, pregnant and lactating women, allergic to Articaine and NSAIDs, active systemic disease, immune-compromised patients, taken analgesics in last 24 h, root fractures, restoration extending to pulp10 and periapical pathologies (except periodontal ligament widening).Preoperatively pain was recorded using Heft Parker VAS (Visual Analog Scale). Cold testing, palpation, percussion and EPT were carried out. 40 patients having symptomatic irreversible pulpitis were randomly divided into 4 groups: group 1 Placebo (n = 10), group 2-Diclofenac patch (n = 10), group-3 Ibuprofen tablets (n = 10), group 4-Paracetamol tablets (n = 10). After 1 h of premedication, all patients were administered IANB injection using 4% Articaine (Septanest with adrenaline 1/100000, Septodont, France) containing epinephrine 1:100000. 15 mins after administration of IANB, patients were asked about symptomatic numbness and was tested with Endo frost and EPT and Outcome was recorded. If lip numbness was present, Electric Pulp Testing and Cold Test give negative result then endodontic access opening was performed and pain was recorded using visual analog scale. The study was conducted for a period of 1.5 years. Results: During the access cavity preparation only 1 subject in the Group III reported pain while in other groups none of the subjects reported pain of any type. When the intergroup comparison was made of intensity of pain 15 min after LA and during access cavity preparation, the difference between the groups was statistically non-significant when analyzed using One Way ANOVA. The intragroup comparison between three time intervals revealed significant reduction in the pain scores from the pre-treatment levels in all the four groups. Conclusions: The results of the study showed that there is no significant effect of different premedication agents on the efficacy of 4% Articaine in teeth with symptomatic irreversible pulpitis.